ID: 129. Issue 4 (April 2016) - Wu, X; Xu, X; Garcia, JG; Wang, T
Abstract : Introduction: Particulate matter (PM) is significantly associated with cardiopulmonary morbidity and mortality. We previously demonstrated that PM induces endothelial barrier disruption via reactive oxygen species (ROS)-dependent mechanisms. This study is focused on characterization of PM-regulated endothelial dysfunction via connexin43 (Cx43), a Gap junction protein. Gap junction is designated as intercellular channel which allows cells to communicate with each other, share nutrients, and transfer chemical or electrical signals, in turn, enables cells in a tissue to function in a coordinated manner. Methods and Results: Cx43 protein levels were evaluated by western blotting, and band density quantified using MyImageAnalysis. Real-time PCR was conducted to determine Cx43 mRNA levels. Human pulmonary artery endothelial cell (EC) barrier function was measured using the electrical cell-substrate impedance sensing (ECIS) system (Applied Biophysics) that provides a readout of transendothelial electrical resistance (TER). PM sample (0.1–0.3 µm of aerodynamic diameter) was collected (April of 2005) from the Ft. McHenry Tunnel, Baltimore, MD using a high-volume cyclone collector. PM (100 µg/ml) induced time-dependent increases in EC Cx43 mRNA levels (∼5 fold increase at 4 hr) and protein expression which was attenuated by N-acetyl-cysteine (NAC, 5 mM, 1 hr pretreatment), an ROS scavenger. Unlike Cx43, Cx37, another connexin expressed in ECs, remained unaltered by PM challenge. In addition, EC pretreatment with a Cx43 inhibitor, connexin-mimetic peptide Gap27 (500 µM, 2 hr pretreatment), significantly attenuated PM-reduced TER reduction by 45%, suggesting a central role of Cx43 in PM-induced lung EC barrier integrity disruption and signal transduction. Conclusions: Our results suggest Cx43 as a key and novel participant in PM-mediated signal transduction that results in loss of vascular barrier integrity. Cx43 may serve as a therapeutic target in PM-induced cardiopulmonary toxicities.